2005
DOI: 10.1007/s00011-005-1386-1
|View full text |Cite
|
Sign up to set email alerts
|

The inhibitory effects of roflumilast on lipopolysaccharide-induced nitric oxide production in RAW264.7 cells are mediated by heme oxygenase-1 and its product carbon monoxide

Abstract: These results suggested that roflumilast exerts its anti-inflammatory effects in macrophages through a novel mechanism that involves the action of HO-1 and its product, CO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…In addition, these observations are in agreement with studies demonstrating that decreasing PDE4 activity with specific inhibitors causes a significant down-regulation in LPS-induced TNF expression and an inflammatory response in vitro and in vivo (Kwak et al, 2005;Ouagued et al, 2005;Hertz et al, 2009). Taken together, these observations strongly suggest that inhibition of LPSinduced up-regulation of PDE4B2 plays a major role in the ability of SAM to attenuate LPS-induced TNF production and related organ injury.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, these observations are in agreement with studies demonstrating that decreasing PDE4 activity with specific inhibitors causes a significant down-regulation in LPS-induced TNF expression and an inflammatory response in vitro and in vivo (Kwak et al, 2005;Ouagued et al, 2005;Hertz et al, 2009). Taken together, these observations strongly suggest that inhibition of LPSinduced up-regulation of PDE4B2 plays a major role in the ability of SAM to attenuate LPS-induced TNF production and related organ injury.…”
Section: Discussionsupporting
confidence: 90%
“…Of importance, in monocytes/ macrophages that predominantly express isoforms of PDE4 A, B, and D, it has been established that PDE4B is involved in LPS-induced signaling mediated by TLR-4 and is essential for LPS-induced TNF expression (Jin and Conti, 2002;Jin et al, 2005). Several studies including ours have shown that LPS-inducible TNF production by monocytes is markedly decreased when PDE activity is blocked by PDE4-specific inhibitors (Kwak et al, 2005;Ouagued et al, 2005;Gobejishvili et al, 2008). Peritoneal and lung macrophages, as well as peripheral leukocytes from Pde4b knockout mice, showed significantly attenuated production of TNF in response to LPS, whereas the responses of Pde4d(Ϫ/Ϫ) mice were similar to those of wild-type mice (Jin and Conti, 2002).…”
Section: Introductionmentioning
confidence: 72%
“…Particularly, cAMP-specific PDE4, which is present in different tissues, is found to be the predominant PDE isoenzyme among 11 PDEs in human monocytes (4,18). Numerous studies have shown that LPS-inducible TNF production by monocytes is markedly decreased when PDE activity is blocked by PDE4-specific inhibitors (3,4,16,23,29,30,31,33,35). PDE4 isozyme has four isoforms, namely A, B, C, and D (18).…”
mentioning
confidence: 99%
“…We previously reported that inducible NOS and HO-1/2 expression is involved in the secretion of IGF-I in MCF-7 cells [52]. Furthermore, expression of the cellular protection and oxidative stress resistance protein HO-1/2 is decreased in kidneys with RF [53] but recovers after EA [54]. However, our results show that rats with RF-induced hypertension respond to oxidative stress, which is reflected by TBARS, iNOS and HO-1/2 levels, and EA treatment inactivates these proteins.…”
Section: Discussionmentioning
confidence: 99%